To the question of efficiency of application of the mathematical models of thermal stresses forming at solidification and cooling of large capacity alloys - I. A. Trusova (Литьë и металлургия)
There is analyzed the efficiency of using of different mathematical models (material behavior) at calculation of the thermo-stressed state of steel ingots and slugs. There is based the choice of model of the material viscoelastic behavior at calculations of solidification and heating of incompletely solidified ingots.